Double dare - Madigan, Michael, 1949- (Cambridge, MN : Adventure Publications, Inc., 2013)
Cutter's Double Dare Ranch in the San Juan Mountains of Colorado caters to adrenaline junkies like himself, and he has never let an amputated leg slow him down. But as an old enemy bent of revenge uses mercenary tricks and a beautiful pawn to sabotage Cutter's dream, a raging wildfire may prove more deadly.
Keywords: People with disabilities -- Fiction; Extreme sports -- Fiction; Revenge -- Fiction; Wildfires -- Fiction; Amputees -- Fiction; San Juan Mountains Region (Colo. and N.M.) -- Fiction; Colorado -- Fiction; Adventure fiction; Mystery fiction